Harnessing Genetic Engineering and Biotechnology for Personalized Cancer Treatment: Innovations and Challenges - Hussein, Mohsin Nader Merzah; Mubdar, Noor Al-Hoda Hassan; Salem, Mohammed Abdullah Makhlaf; Hussein, Murooj Sattar Ali (American Journal of Biodiversity, 2025)
This study explores the integration of genetic engineering and biotechnology for personalized cancer treatment, addressing the growing demand for targeted and effective therapies. Despite significant advances, a knowledge gap persists in optimizing genetic modifications to enhance treatment efficacy while minimizing side effects. This research utilizes next-generation sequencing and CRISPR-Cas9 technology to identify genetic biomarkers and develop personalized therapeutic strategies. Findings reveal that precision medicine enabled by genetic profiling significantly improves patient outcomes and reduces adverse reactions. The results underscore the potential of personalized cancer treatments to revolutionize oncology by tailoring therapies to individual genetic profiles. These implications highlight the need for collaborative efforts in research, regulatory frameworks, and ethical considerations to accelerate the adoption of personalized medicine in clinical practice.